ANALISA DAN PERANCANGAN SISTEM INFORMASI PEMESANAN SABLON BERBASIS ANDROID (STUDI KASUS SATRIA SABLON KENDAL) - Murwatisari, Lisyah Antika; Soelistijadi, R (Information Technology and Telematics, 2018)
Abstract – Satria Sablon is one of the screen printing order business located in Kendal Regency, which provides varius kinds of screen printing items that can be ordered. The purpose of application. The method used to build syatem development design using object-oriented design analysis with UML (Unified Modeling Language), while for software (Software) used in building systems using the Android Studio program and for database using the MySQL Database. The results of the study produce a usecase and class diagram.